Pengaruh Variasi Ukuran Mesh Terhadap Nilai Kalor Briket Arang Tempurung Kelapa - Sabindo, La Ode; Kadir, Kadir; Hasbi, Muhammad (Teknik Mesin Universitas Halu Oleo, 2020)
Energy demand and consumption is currently increasing and is focused on the use of fuel oil and gas whose prices are increasing and reserves are very limited. One alternative energy that needs to be developed through processing agricultural waste is briquette fuel. The raw material for briquettes used in this study is coconut shell. The purpose of this study was to determine the effect of variations in mesh size on the thermal characteristics of coconut shell charcoal briquettes. The research method used in the form of experiments with the stages of the implementation of the coconut shell made and crushed and sifted using 20, 30 and 40 mesh sieves and using starch adhesive 10 % of the weight of raw materials with a pressure of 100 kgf/cm². The results showed that the smaller the particle size, the higher the heating value of 6118.49 cal/g. 8.45% moisture content, 2.56 % ash content, 13.28 % fly substance and 75.71 % bonded carbon. The conclusion of this research is the level of thermal characteristics of coconut shell charcoal briquettes is influenced by particle size, the smaller the particle size, the higher the heating value produced.Keywords: Briquette, coconut shell, starch, particle size